The Classification of Social and Cultural Risks - Anna MAYAKOVA (Communications of International Proceedings, 2020)
The article introduces author's classification of risks that has been formed in virtue of the author's previous research as well as the works of scientists and specialists of economic (Batova I., Acharya V., Pedersen L., Philippon T., Richardson M., Semernik S., Cristea G., Constantinescu D.), sociological (Grimov O.A., Kamensky E.G., Shestopal E. B., Selezneva A.B.), technical (Khodydevskaya S.V., Khalin V.G., Chernova G.V.), psychological (Molokostova A.M.) and other scientific spheres. Within the framework of the study the characteristics of the classification (type of risk, the risk content, cause (source) of the risk, the direction of risk, degree of risk impact, the probability of the risk occurring, risk function, level of risk, the trend manifestation of risk, form of risk) and corresponding with them types of risk have been defined. The classification of social and cultural risks offered is a universal one to use in different spheres of science and for practical use.
Keywords: Risk · Social and Cultural Risk · Classification of Risks · Type of Risk · Characteristic of Classification.